TECHNOLOGY AND CHANGE IN RELIGIOUS BELIEF - Sweet, William (Journal of Dharma, 1993)
Does technology have an effect on religious belief? The answer seems to be clearly in the affirmative. It is obvious that, in western industrialized nations at least, people no longer believe in God as they once did, and the presumption of technology having such an effect explains the constant attempts on the part of believers over the last 400 years to show the compatibility of religion and technology (Goldman (1990): 49). The advancement of technology, then, appears to have been accompanied by a change in (if not an abandonment of) religious belief. But how, one might ask, does technology lead to change in religious belief and, more importantly, why? Furthermore, what should the response of the believer be to technology?